Il trattamento integrato delle psicosi - Santomauro, Sandra (Il sogno della farfalla, 2016)
Currently, a growing number of psychotherapists consider psychodynamic psychotherapy as the main approach to the integrated treatment of psychoses in the public health service. Referring to the Birth Theory as fundamental professional training for psychotherapists, the treatment of a severe illness may be rather similar either in a private practice or in the public mental health service. The author clarifies the differences between both areas and considers the possibilities and limits of other kinds of psychotherapies or activities recommended by the official guidelines.